Rethinking clinical decision-making to improve clinical reasoning - Corrao, Salvatore; Argano, Christiano (Frontiers in Medicine, 2022)
Improving clinical reasoning techniques is the right way to ameliorate decision-making from different point of views: prognostic, diagnostic, and therapeutic ones. However, the process to do that is to fill knowledge gaps by studying and growing experience, and to know some cognitive aspects to raise the awareness of thinking mechanisms to avoid cognitive errors by a correct educational training. In this article the authors examine some current situations regarding clinical approach and educational gaps in the context of the training of medical students and young doctors. They examine the core elements of clinical reasoning including metacognition, reasoning errors and cognitive biases, reasoning strategies and ways to improve decision-making. The article addresses the dual-process theory of thought and the new Default Mode Network concept. The reader may consider the article as a first level guide to deepen how to think and not what to think, knowing that this synthesis represents the result of years of study and reasoning in a clinical practice and educational setting.